2020
DOI: 10.3389/fimmu.2020.572858
|View full text |Cite
|
Sign up to set email alerts
|

Th17/Treg-Related Transcriptional Factor Expression and Cytokine Profile in Patients With Rheumatoid Arthritis

Abstract: ObjectivesThe aim of our study was to determine whether there is a correlation between transcription factors expression and Th17/Treg ratio, cytokine profile in the RA phenotype as well as to identify transcription factors that could be a potential biomarker for RA.MethodsThe study was conducted on 45 patients with RA, 27 patients with OA and 46 healthy controls (HCs). Th17 and Treg frequency was determined by flow cytometry (15 patients with RA/OA and 15 subjects of HC). Gene expression was estimated by qPCR,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
65
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(71 citation statements)
references
References 53 publications
(46 reference statements)
5
65
0
1
Order By: Relevance
“…RA was classically considered a T H 1-mediated disease [ 59 ]. However, recent studies have suggested that increased T H 17 and T H 22 activities and dysfunctional T reg also play a role in the pathogenesis of RA [ 60 , 61 ]. Individuals with certain genetic variations of the human leukocyte antigen (HLA) genes are known to be susceptible to RA, while the only well-established environmental risk factor of RA is cigarette smoking [ 62 ].…”
Section: Evidence On Vitamin D For Prevention and Treatment Of Rheumatic Diseasesmentioning
confidence: 99%
“…RA was classically considered a T H 1-mediated disease [ 59 ]. However, recent studies have suggested that increased T H 17 and T H 22 activities and dysfunctional T reg also play a role in the pathogenesis of RA [ 60 , 61 ]. Individuals with certain genetic variations of the human leukocyte antigen (HLA) genes are known to be susceptible to RA, while the only well-established environmental risk factor of RA is cigarette smoking [ 62 ].…”
Section: Evidence On Vitamin D For Prevention and Treatment Of Rheumatic Diseasesmentioning
confidence: 99%
“…Interestingly, the implication of this cytokine in joint-related pathologies seems to be dual and its use as a therapeutic target may be approached in a modulatory manner as contra-dictory data were addressed regarding this cytokine in this particular context. For instance, Paradowska-Gorycka et al found that patients affected with RA or osteoarthritis have higher serum levels of IL-2 than the healthy controls [97], whereas Wang et al reported an opposite trend, as the serum level of IL-2 was downregulated in RA patients group compared with healthy one [98].…”
Section: Micro-immunotherapy: a Multiple Immune-targeted Ultra-low-dose-based Strategy To Calm Chronic Inflammation In Ramentioning
confidence: 99%
“…Among them, Th17 cells can highly secrete inflammatory cytokines such as IL-17, IL-6 and IL-22, mediating inflammatory reactions and autoimmune reactions in the body [ 51 ]. Abnormal activation of Th17 cells will cause the imbalance of Th17/Treg cells and play a key role in autoimmune diseases such as RA, especially in local inflammatory response and bone destruction, while long-term local inflammation will induce and worsen the destruction of RA articular cartilage [ 52 ]. Cells in the body can not only sense the stimulation of various chemical factors in the external environment but also live in various mechanical environments, such as the pressure of fluid as well as shear stress caused by the fluid flow.…”
Section: Discussionmentioning
confidence: 99%